Interval Kepercayaan untuk Selisih Dua Koefisien Variasi dari Distribusi Invers Gaussian Berdasarkan Metode MOVER - Siti Fadhilah Irawan; Abdul Kudus (UNISBA Press, 2024)
Abstract. The estimation of parameters from the Inverse Gaussian (IG) distribution, which describes data with positive skewness or right skewness (positive skew), requires us to estimate the difference between two CVs (coefficients of variation) from two IG-distributed populations. The estimation of the difference between two CVs can be performed using confidence intervals or interval estimators. One method available is the interval estimator using the Method of Variance Estimate Recovery (MOVER). The MOVER method itself is one of the methods for constructing intervals and will be applied to PM 2.5 air quality data in Semarang City and Malang City. This is because, based on preliminary analysis of several cities in Indonesia, the data that meets the criteria of having positive skewness or right skewness is found in Semarang City and Malang City. In this thesis, the MOVER method is applied to the coefficient of variation from the IG distribution on PM 2.5 air quality data. The research process includes steps such as calculating parameter estimates from the IG distribution using the maximum likelihood method, conducting a Kolmogorov-Smirnov goodness-of-fit test, and then calculating the 95% confidence interval using the MOVER method. Based on the calculations, it was found that the PM 2.5 air quality data in Semarang City and Malang City for the year 2023 is well-modeled by the IG distribution, and the 95% confidence interval for the CV using the MOVER method for that data lies within the range [-0.1452; 0.0170] with an interval length of 0.1622. It is observed that the confidence interval contains the value 0, indicating that the difference in CV is not significant. Abstrak. Penaksiran parameter dari distribusi Invers Gaussian (IG) yang menggambarkan data yang memiliki kemiringan positif atau miring ke sebelah kanan (skew positif). Maka kita harus dapat menduga selisih dua CV dari dua populasi distribusi IG. Pendugaan selisih dua CV dapat dilakukan dengan menggunakan interval kepercayaan atau penduga interval. Salah satu metode yang ada yaitu penduga interval kepercayaan pendugaan menggunakan metode The Method of Variance Estimate Recovery (MOVER). Metode MOVER sendiri merupakan salah satu metode untuk membuat interval. yang akan diterapkan pada data kualitas udara PM 2.5 di Kota Semarang dan Kota Malang. Karena dari hasil analisis sementara beberapa kota di Indonesia, data yang memenuhi dan memiliki kemiringan positif atau condong kekanan yaitu Kota Semarang dan Kota Malang. Dalam skripsi ini dilakukan penerapan metode MOVER untuk koefisien variasi dari distribusi IG pada data kualitas udara PM 2.5. Dalam proses penelitian tahapan analisis yang dilakukan meliputi menghitung taksiran parameter dari distribusi IG menggunakan metode maksimum likelihood, melakukan uji kecocokan Kolmogorov-Smirnov, kemudian menghitung selang kepercayaan 95% dengan metode MOVER. Berdasarkan hasil perhitungan diperoleh bahwa data kualitas udara PM 2.5 di Kota Semarang & Kota Malang tahun 2023 cocok dimodelkan dengan distribusi IG dan selang kepercayaan MOVER dengan tingkat kepercayaan 95% untuk KV dari data tersebut berada diantara rentang [ - 0,1452 ; 0,0170 ] dengan Panjang interval sebesar 0,1622. Terlihat bahwa interval kepercayaannya mengandung nilai 0 , artinya selisih KV-nya tidak signifikan.